Grazing management for wildlife benefits: a planning framework using integrated ecological tools for development of wildlife-oriented grazing strategies - McFarland, Stuart C., author (Colorado State University. Libraries, 2010)
Many traditional rangeland and domestic livestock management guidelines have focused on uniform livestock distribution, often causing simplification of heterogeneous landscapes, with a goal of improvement/maintenance of rangeland function at "climax" conditions. Often it is assumed that proper rangeland management parallels proper management of the wild animals utilizing rangeland habitat. However, wildlife benefits derived from the ecological conditions created by various grazing strategies are typically limited and largely coincidental. This paper will examine 1) the concept of spatiotemporal heterogeneity and its value to wildlife, 2) how existing tools could be integrated to support wildlife‐oriented rangeland planning, 3) how these concepts and tools could be applied with a planning framework, and 4) recognition of some limitations with possible opportunities for refinement and future research.
Keywords: wildlife-oriented rangeland planning; rangeland management; livestock; grazing; spatiotemporal heterogeneity; conservation; Range management; Wildlife conservation; Livestock